Emerging Role of Mesenchymal Stem Cell-derived Exosomes in Regenerative Medicine - Zhao, Ting; Sun, Feng; Liu, Jinwen; Ding, Tianyan; She, Jie; Mao, Fei; Xu, Wenrong; Qian, Hui; Yan, Yongmin (Current stem cell research & therapy, 2019)
Recent studies have shown the great value of cell therapy over the past few decades. Mesenchymal stem cells (MSCs) have been reported to treat various degenerative diseases not through their differentiation potential but through their paracrine factors of the extracellular vesicle (EV) including exosomes. Exosomes are nanosized (70~150 nm) membrane-bound extracellular vesicles, not only involved in cell-to-cell communication but also in the development of tissue injury repair. As more researchers proved the enormous potential of exosomes in the field of repairing damaged tissue currently, it is urgent to explore the concrete mechanism and make exosomes to be a practical treatment tool in clinical medicine. In our study, we analyzed and summarized the work on tissue repair via exosomes in order to give some suggestions about the application of exosomes in clinical reality in the future. MSC-derived exosomes (MSC-Ex) contain a wide variety of functional proteins, mRNAs, miRNAs and signaling lipids. Compared with their parent cells, MSC-Ex are more stable and can reduce the inherent safety risks in administering viable cells such as the risk of occlusion in microvasculature. MSC-Ex can be used to develop a cell-free exosome-based therapy for regenerative medicine, and may provide an alternative to MSC-based therapy. This review summarizes the most recent knowledge of therapeutic potential of MSC-Ex in the liver, heart, kidney, bone, brain diseases and cancer, as well as their associated challenges and opportunities.